2007
DOI: 10.1007/s10389-007-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

Health risks in tobacco farm workers—a review of the literature

Abstract: Aim To systematically describe and summarize the specific occupational health impact of tobacco farm working. Subjects and methods Qualitative systematic review applying a standardized electronic literature search strategy (MEDLINE, TOXNET, EMBASE, AGRICOLA, Science Citation Index; until January 2007) and hand search within eligible articles. Double assessment of eligibility and study results. Inclusion of all studies on specific work-related health risks of tobacco farm workers, e.g. risk factors for and freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 38 publications
1
40
0
5
Order By: Relevance
“…The signs and symptoms observed among the workers of the region (vomit, nausea, headache and dizziness) were also described by Arcury et al 2,3,4 during tobacco production in Hispanic farmworkers in the USA. In our study, case-patients were identified during the period of tobacco harvesting in the region, when greatest exposure of the farmers to the nicotine in the tobacco leaves occurs 5,6,10 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The signs and symptoms observed among the workers of the region (vomit, nausea, headache and dizziness) were also described by Arcury et al 2,3,4 during tobacco production in Hispanic farmworkers in the USA. In our study, case-patients were identified during the period of tobacco harvesting in the region, when greatest exposure of the farmers to the nicotine in the tobacco leaves occurs 5,6,10 .…”
Section: Discussionmentioning
confidence: 99%
“…The condition has not been reported in any country of the Latin American region or in Brazil, which is the second largest tobacco producer in the world 6 with more than 190,000 family farmer families involved in the farming of tobacco.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations